Trait aggression affects the response inhibition to angry expressions: An event-related brain potential study. (1st January 2020) - Sun, Lijun; Niu, Gengfeng; Li, Junyi; Du, Hongqin; Hu, Xiangen; Yang, Shichang; Luo, Yanyan
Abstract: Response inhibition to angry expressions is impaired in individuals with high trait aggression. Yet, the underlying cognitive neural mechanism of it remains unclear. The present study aimed to investigate the underlying cognitive neural mechanisms of response inhibition to angry expressions in individuals with high trait aggression and whether there was emotion-specificity of response inhibition in individuals with high trait aggression. 58 individuals (29 participants with high trait aggression) completed an emotional Go/NoGo task, during which participants' EEG were recorded. Results indicated that individuals with high trait aggression showed smaller NoGo P3 effect than individuals with low trait aggression, in particular facing angry or fearful expressions. These results suggest that individuals with high trait aggression show deficits in response inhibition, in particular facing angry expressions, and these deficits exist in the later stage of response inhibition, which is closely related to the actual inhibition of the motor system; there is no emotion-specificity of response inhibition in individuals with high trait aggression. Highlights: Individuals with high trait aggression (HTA) have deficits in response inhibition. Individuals with HTA have deficits in response inhibition to angry expressions. This mechanism relies on the later stage of response inhibition to angry expressions. There was no emotion-specificity of response inhibition in individuals with HTA.